SCHOOL FACTORS CAUSING ANXIETY FOR ADOLESCENTS IN VIETNAMESE SECONDARY SCHOOLS: AN EMPIRICAL STUDY - Dinh, Hong-Van Thi; Do, Le-Hang Thi (International Journal of Psychosocial Rehabilitation, 2020)
Anxiety is regarded as an emotion characterized by feelings of tension, worried thoughts and physical changes like increased blood pressure and it is a common phenomenon for people in general and for adolescents in particular. The study aimed to find out the factors that cause anxiety among adolescents in Vietnam under the influence of gender and grade. A group of 749 Vietnamese secondary school students participated in the survey. Results showed that scores and exams caused the most anxiety for participants. Factors related to scores and exams created more anxiety for females than males. Factors related to communicating with friends, teachers, school/classroom facilities, and school safety caused more anxiety for students in grades 6, 7, and 8 than those in grade 9. Our study suggests that programs prevention and intervention should be considered to minimize anxiety for adolescents from the pressure of scores, exams as well as the impact of sex and grade.